In vivo targeting of metastatic breast cancer via tumor vasculature-specific nano-graphene oxide. (October 2016) - Yang, Dongzhi; Feng, Liangzhu; Dougherty, Casey A.; Luker, Kathryn E.; Chen, Daiqin; Cauble, Meagan A.; Banaszak Holl, Mark M.; Luker, Gary D.; Ross, Brian D.; Liu, Zhuang; Hong, Hao
Abstract: Angiogenesis, i.e. the formation of neovasculatures, is a critical process during cancer initiation, progression, and metastasis. Targeting of angiogenic markers on the tumor vasculature can result in more efficient delivery of nanomaterials into tumor since no extravasation is required. Herein we demonstrated efficient targeting of breast cancer metastasis in an experimental murine model with nano-graphene oxide (GO), which was conjugated to a monoclonal antibody (mAb) against follicle-stimulating hormone receptor (FSHR). FSHR has been confirmed to be a highly selective tumor vasculature marker, which is abundant in both primary and metastatic tumors. These functionalized GO nano-conjugates had diameters of ∼120 nm based on atomic force microscopy (AFM), TEM, and dynamic laser scattering (DLS) measurement. 64 Cu was incorporated as a radiolabel which enabled the visualization of these GO conjugates by positron emission tomography (PET) imaging. Breast cancer lung metastasis model was established by intravenous injection of click beetle green luciferase-transfected MDA-MB-231 (denoted as cbgLuc-MDA-MB-231) breast cancer cells into female nude mice and the tumor growth was monitored by bioluminescence imaging (BLI). Systematic in vitro and in vivo studies have been performed to investigate the stability, targeting efficacy and specificity, and tissue distribution of GO conjugates. Flow cytometry and fluorescence microscopy examination confirmed the targeting specificity of FSHR-mAb attached GO conjugates against cellular FSHR. More potent and persistent uptake of 64 Cu-NOTA-GO-FSHR-mAb in cbgLuc-MDA-MB-231 nodules inside the lung was witnessed when compared with that of non-targeted GO conjugates ( 64 Cu-NOTA-GO). Histology evaluation also confirmed the vasculature accumulation of GO-FSHR-mAb conjugates in tumor at early time points while they were non-specifically captured in liver and spleen. In addition, these GO conjugates can serve as good drug carriers with satisfactory drug loading capacity (e.g. for doxorubicin [DOX], 756 mg/g). Enhanced drug delivery efficiency in cbgLuc-MDA-MB-231 metastatic sites was demonstrated in DOX-loaded GO-FSHR-mAb by fluorescence imaging. This FSHR-targeted, GO-based nanoplatform can serve as a useful tool for early metastasis detection and targeted delivery of therapeutics. Graphical abstract: